Development and validation of the perceived university employment support scale among undergraduate students - Ye, Jianmei; Huang, Dawei; Meng, Sujie; Long, Chunlan; Zhang, Yukun; Liu, Ling (Frontiers in Psychology, 2025)
IntroductionGrounded in social support theory, this study aims to develop and validate the Perceived University Employment Support Scale (PUESS) to systematically evaluate the role of higher education institutions in facilitating graduates’ successful transition into the labor market.MethodsTwo studies were conducted to develop and validate the PUESS. Study 1 involved item generation, preliminary selection, and initial validation based on exploratory analyses. Study 2 further tested the construct validity, criterion-related validity, and measurement invariance of the finalized 20-item scale. Data were collected from diverse samples of university graduates to ensure representativeness.ResultsThe PUESS demonstrated strong internal consistency and robust construct validity across studies. The scale also showed comparable criterion-related validity to the University Student Social Support Scale and exhibited measurement invariance across gender, educational levels, and institutional types.DiscussionThe findings provide empirical support for understanding how university-based employment support contributes to graduates’ career development. The PUESS offers a reliable and practical tool for assessing institutional employment support and provides actionable insights for education administrators and policymakers aiming to enhance employment services in higher education.